Does market competition affect all banks equally? Empirical evidence on Montenegro - Nina Vujanović; Nikola Fabris (Journal of Central Banking Theory and Practice, 2021)
Bank stability is an important aspect of financial stability, especially in bank-centric systems like that of Montenegro. Hence, it is important to analyse risks affecting stability of both the banking and financial system as a whole. Rising competition among banks could pose a challenge and possibly change the level of credit risk, especially if the banks are small in size. This can affect both credit risk and financial stability. Small-sized banks could be the ones to react less nimbly to a changing market structure than bigger banks with stable market shares. This study tries to answer whether competition affects credit risk in Montenegro and whether banks differing in size react differently. Panel data techniques were applied to eleven banks which account for over 90 percent of the banking sector. The results indicate that market concentration could be particularly harmful when it comes to credit risk of small-sized banks, while large-sized banks are less affected. Overall, the increasing competition may positively affect credit risk in Montenegro.
Keywords: G21; G28; 330; credit risk; bank competition; financial stability